# How do you find #(f*g)(-1)# given #f(x)=x^2-1# and #g(x)=2x-3# and #h(x)=1-4x#?

(f * g)(-1) = (f(-1)) * (g(-1)) f(-1) = (-1)^2 - 1 = 0 g(-1) = 2 * (-1) - 3 = -5 (f * g)(-1) = 0 * (-5) = 0

By signing up, you agree to our Terms of Service and Privacy Policy

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you find the domain and range of a function in interval notation?
- How do you simplify #5-6 times 9 div 7 / 3# using PEMDAS?
- How do you simplify #25-8times2+3^2# using order of operations?
- How do you evaluate #9^2+5times4#?
- $5400 is invested, part of it at 12% and part of it at 9%. For a certain year, the total yield is 576.00. How much was invested at each rate?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7